Pengaruh Desain Atmosfer Toko terhadap Perilaku Belanja: Studi atas Pengaruh Gender terhadap Respon Pengunjung Toko - Kusumowidagdo, Astrid (Universitas Prasetiya Mulya, 2010)
The design of store atmosphere shall function as kind of stimuli that will attract the visitor to decide which store to choose. Further, it is aimed to evoke the desire of customers to purchase and create transaction. Thus, it can directly affect the shopping behaviour of both men and women. This study will learn about how the atmospheric stimuli can affect the behaviour of visitor, both men and women. The study is divided into two stages: the first stage, exploratory research design; the second stage, path analysis. The exploration or identification attributes is done through interview according to the attributes of atmospheric stimuli (Turley and Milliman). While the endogenous variable in this case are the organism (visitor) and respond (of visitor). Atmospheric stimuli factors, in the other hand shall function as exogenous variables. While the result of the study conducted to 107 respondents of men and women shows that store exterior, interior lay out and human variables are siginificant to the variable of consumber respons. Store exterior, store interior have such a siginificant effect on the organism (the emotional intensity of male visitor). Organism variable has an effect on the responds of male visitors, while store interior variable only affect siginificantly on the organism of female visitor (the emotional intensity of female visitors).